Patient and Professional Factors That Impact the Perceived Likelihood and Confidence of Healthcare Professionals to Discuss Implantable Cardioverter Defibrillator Deactivation in Advanced Heart Failure: Results From an International Factorial Survey. Issue 6 (November 2018) - Hill, Loreena; McIlfatrick, Sonja; Taylor, Brian J.; Jaarsma, Tiny; Moser, Debra; Slater, Paul; McAloon, Toni; Dixon, Lana; Donnelly, Patrick; Stromberg, Anna; Fitzsimons, Donna
Abstract : Background: Rate of implantable cardioverter defibrillator (ICD) implantations is increasing in patients with advanced heart failure. Despite clear guideline recommendations, discussions addressing deactivation occur infrequently. Aim: The aim of this article is to explore patient and professional factors that impact perceived likelihood and confidence of healthcare professionals to discuss ICD deactivation. Methods and Results: Between 2015 and 2016, an international sample of 262 healthcare professionals (65% nursing, 24% medical) completed an online factorial survey, encompassing a demographic questionnaire and clinical vignettes. Each vignette had 9 randomly manipulated and embedded patient-related factors, considered as independent variables, providing 1572 unique vignettes for analysis. These factors were determined through synthesis of a systematic literature review, a retrospective case note review, and a qualitative exploratory study. Results showed that most healthcare professionals agreed that deactivation discussions should be initiated by a cardiologist (95%, n = 255) or a specialist nurse (81%, n = 215). In terms of experience, 84% of cardiologists (n = 53) but only 30% of nurses (n = 50) had previously been involved in a deactivation decision. Healthcare professionals valued patient involvement in deactivation decisions; however, only 50% (n = 130) actively involved family members. Five of 9 clinical factors were associated with an increased likelihood to discuss deactivation including advanced age, severe heart failure, presence of malignancy, receipt of multiple ICD shocks, and more than 3 hospital admissions during the previous year. Furthermore, nationality and discipline significantly influenced likelihood and confidence in decision making. Conclusions: Guidelines recommend that healthcare professionals discuss ICD deactivation; however, practice is suboptimal with multifactorial factors impacting on decision making. The role and responsibility of nurses in discussing deactivation require clarity and improvement. Abstract : Supplemental digital content is available in the text.